Knowledge, attitude, and practice of ergonomics among physiotherapy undergraduates in Malaysia - Deepashini Harithasan,; Alif Najmi Amaluddin,; Devinder Kaur Ajit Singh, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Ergonomic posture can be defined as neutral positions of the body that is aligned and balanced while either sitting or standing, placing minimal stress on the body and keeping joints aligned. A good posture can help to prevent musculoskeletal disorders (MSDs). However, MSD cases are the most common health problem among physiotherapists including undergraduates. The aim of this study was to identify the knowledge, attitude, and practice of ergonomics among physiotherapy undergraduates in Malaysia. An online survey involving 116 physiotherapists undergraduates from learning institutions all over Malaysia was conducted. All the participants were provided a Google Form comprising 18 questions about demographic data, knowledge, attitude, and practice. The data were analyzed using the frequency table and chi-square test. Out of 116 respondents, 76.72% had good knowledge of ergonomics, almost all the respondents accounting for 96.35% had a positive attitude towards ergonomics, and 82.55% practiced good ergonomics. A statistically significant association was shown between attitude and level of education (p<0.05) and year of study (p<0.05), and knowledge with the year of study (p<0.05). The results showed that physiotherapy undergraduates in Malaysia have good knowledge and positive attitude towards ergonomics and they practiced good ergonomics in their working life.